Fremmede her på jorden - Afrofuturistiske spekulationer - Steinskog, Erik (K&K - Kultur og Klasse, 2015)
The last couple of decades have seen an increase in research and artistic practices around afrofuturism. Taking the cue from Mark Dery’s article “Black to the Future,” where he coins the term, the article points to different aspects of afrofuturism. The music and philosophy of Sun Ra is an important point of departure, having ancient Egypt and a future outer space as orientation. At the same time there are, as Dery makes clear, other dimensions at stake. Following Dery’s argument that African Americans and other Afrodiasporic citizens in a specific sense are descendent from alien abductees, the article moves into relations between time and history, and employs an afrofuturist lens to discuss how speculative fiction can be used in interpreting history, illustrating a kind of science fiction historiography. As a case in point the Middle Passage, and the chronotope of the ocean, is discussed in tandem with Nnedi Okorafor’s novel Lagoon. Okorafor’s novel also testifies to an expansion of afrofuturism with increasing expressive work coming from the African continent.